Bubble growth in composite water/fuel droplets: Effect on timing of their puffing/micro-explosion - Chernov A. A. Andrey Aleksandrovich; Antonov D. V. Dmitry Vladimirovich; Pavlenko A. N. Aleksandr Nikolaevich; Bar-Kohany T. Tali; Strizhak P. A. Pavel Alexandrovich; Sazhin S. S. Sergey Stepanovich (2025, 2025)
Title screen